2021
DOI: 10.31681/jetol.932682
|View full text |Cite
|
Sign up to set email alerts
|

Teaching writing skills in EFL classes with blending learning

Abstract: Blended learning has become an emerging trend in the field of education and has caught the attention and interest of many researchers as a new approach to encourage students in their learning process, especially during COVID-19 disruption. Blended learning is also known as 'hybrid learning', 'mixed-learning or 'flipped learning' in the literature. The purpose of this study was to investigate the effect of blended learning for improving EFL students', from the eleventh grade, English writing skills and the stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 12 publications
1
10
0
Order By: Relevance
“…Elementary [54] Junior High [65,75] Senior High [55,62,67,72] Secondary Not Specified [64] It is evident from Table 4 that MABL in EFL is particularly favored in higher education research, with a total of 16 studies conducted with university students as the research participants. In the majority of studies [24, 53, 56, 59-61, 63, 66, 68-70, 73], researchers employed MABL in a specific or comprehensive four-skill English language course and validated its effectiveness.…”
Section: Education Level Studymentioning
confidence: 99%
See 4 more Smart Citations
“…Elementary [54] Junior High [65,75] Senior High [55,62,67,72] Secondary Not Specified [64] It is evident from Table 4 that MABL in EFL is particularly favored in higher education research, with a total of 16 studies conducted with university students as the research participants. In the majority of studies [24, 53, 56, 59-61, 63, 66, 68-70, 73], researchers employed MABL in a specific or comprehensive four-skill English language course and validated its effectiveness.…”
Section: Education Level Studymentioning
confidence: 99%
“…Among the selected articles, four studies were conducted in a high school context. Three of these studies [62,67,72] aimed to enhance students' English writing skills by utilizing MABL, while the fourth study [55] upgraded MABL to the mobile blended active language learning (MBALL) approach and investigated its impact on the critical reading skills of Thai high school students. Participants in each study demonstrated a positive attitude toward this innovative approach.…”
Section: Education Level Studymentioning
confidence: 99%
See 3 more Smart Citations